Istotność wyborów i jej czynniki w świadomości społecznej - Wojtasik, Waldemar (Political Preferences, 2011)
One of the basic features of a democratic state are cyclical and competitive elections. They are an instrument through which the ideas of political representation are implemented, while being also a factor of creation of various authorities. The specificity of the distribution of power in a democracy is founded on the causative position of the general elections, as a form of granting the most important powers to the institutions of the political system. The present article text presents the results of research on the issue of the social significance of the various elections held in Poland and the factors influencing the perception of their importance. In the course of the study were revealed both the social preferences for the function of distribution of power and influence on the lives of citizens as the most important factors in the perception of the importance a given election. In the case of the least important elections, a key reason for such their perception was the location of the decision-making in other bodies of the political system than the one on which the opinions were expressed.